Providers of Follow-Up Care in a Population-Based Sample of Breast Cancer Survivors - Friese, Christopher R. (2014)
PURPOSE: To describe which providers provide breast cancer survivorship care. PATIENTS AND METHODS: We conducted a longitudinal survey of non-metastatic breast cancer patients identified by the SEER registries of Los Angeles and Detroit. Multinomial logistic regression examined the adjusted odds of surgeon compared with a medical oncologist follow up or primary care provider compared with medical oncologist follow up, adjusting for age, race/ethnicity, insurance, tumor stage, receipt of chemotherapy, endocrine therapy use, and visit to a medical oncologist at the time of diagnosis. Results were weighted to account for sample selection and non-response. RESULTS: 844 women had invasive disease and received chemotherapy or endocrine therapy. 65.2% reported medical oncologists as their main care provider at four years, followed by PCP/other physicians (24.3%) and surgeons (10.5%). Black women were more likely to receive their follow-up care from surgeons (OR 2.47, 95% CI 1.16–5.27) or PCP/other physicians (OR 2.62, 95% CI 1.47–4.65) than medical oncologists. Latinas were more likely to report PCP/other physician follow up than medical oncologists (OR 2.33, 95% CI 1.15–4.73). Compared with privately-insured women, Medicaid recipients were more likely to report PCP/other physician follow up (OR 2.52, 95% CI 1.24–5.15). Women taking endocrine therapy four years after diagnosis were less likely to report surgeons or PCP/other physicians as their primary provider of breast cancer follow up care. CONCLUSIONS: Different survivorship care patterns based on race/ethnicity and insurance status. Interventions are needed to inform patients and providers on the recommended sources of breast cancer follow up.